Recuperando espaços de emancipação na história de vida de ex-alunas de escola comunitária luterana - Ulrich, Claudete Beise (2006)
This dissertation has the purpose of retrieving the spaces of emancipation in the life stories of former female students of Lutheran community schools in Brazil. Initially the author tries to understand the concepts of liberation, emancipation, rational autonomy and Christian freedom. On the basis of the texture of the theoretical-conceptual threads, the concept of human emancipation is taken in this dissertation as a synthetic category that is peculiar to the analytical-synthetic movement of the dialectical approach. The second chapter describes the theoretical-methodological approach, which is based on an ethnographic perspective, permeated by a feminist methodology and the gender referent. The author uses the life story as research technique, aiming at a narrative investigation that highlights subjectivity, daily life and memory. The third, fourth, fifth and sixth chapters present the life stories told by the former females students, Anneliese, Ruth, Renita and Yvonne. The last chapter tries to identify spaces of emancipation in their life stories: the immigration process, childhood memories, adolescence memories, the educational processes in the family, the Lutheran community school, the Lutheran church, in other educational spaces, professional training, the constitution of their own family, their image of God, Bible reading, participation and leadership in community and/or congregational groups until 2005. Their narratives reveal a deep influence of the education they received in the community school and in the Lutheran church, bearing on the achievement or non-achievement of emancipatory spaces. By allowing their memories to be recorded and published, the narrators prove to be sages and educators, making it possible to reflect on the importance of religion and education in emancipation processes. The dissertation then concludes by discussing how the emancipation processes take place in the historical daily lives and by emphasizing that this process is a plural, collective, conflictive and dialectical one, for it points to the unfinished nature of human life.